Menanam Ilmu Akuntansi, Menuai Nilai Kejujuran - Fransiskus Korosando (Program Studi Pendidikan Ekonomi, Universitas Flores, 2016)
Character-oriented education now is the time to be implemented seriously, because there are indications of a decline in the quality of education graduates, which is marked by a decline in the value of honesty. Character-oriented learning patterns are seen as able to stimulate students, so that character will be formed which contains the value of glory so that quality human resources will be realized. Implicit accounting lectures, in fact, recommended the management of non-manipulative (honest) attitudes and responsibilities. Honesty can be demonstrated through the attitude and action of stating something truly, as it is based on authentic evidence, not reducing and markuping financial data, adhering strictly to the standard procedures of financial accounting that apply in Indonesia. Habituating an honest attitude and acting honestly will make them as individuals who will gain the trust of others. If it is well embedded in every student, then it is worth a social achievement obtained, called an individual who can be trusted, carry out the mandate of many parties. This is the trait that every student needs to have, as an image of personality and even national identity.